2019
DOI: 10.3390/molecules25010060
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Transformation of Licochalcones

Abstract: Microbial transformation of licochalcones B (1), C (2), D (3), and H (4) using the filamentous fungi Aspergillus niger and Mucor hiemalis was investigated. Fungal transformation of the licochalcones followed by chromatographic separations led to the isolation of ten new compounds 5-14, including one hydrogenated, three dihydroxylated, three expoxidized, and three glucosylated metabolites. Their structures were elucidated by combined analyses of UV, IR, MS, NMR, and CD spectroscopic data. Absolute configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Biocatalysis is considered to be green and eco-friendly technology, which has sustainable development prospects [17]. Since 2000, a variety of microorganisms have exhibited abilities to convert flavonoids, and some microorganisms were also found to naturally and directly synthesize flavonoids as a result of their own endogenous metabolism [18]. The biocatalytic production of flavonoids offers many advantages, such as fast production, low environmental pollution, and large-scale production.…”
Section: Introductionmentioning
confidence: 99%
“…Biocatalysis is considered to be green and eco-friendly technology, which has sustainable development prospects [17]. Since 2000, a variety of microorganisms have exhibited abilities to convert flavonoids, and some microorganisms were also found to naturally and directly synthesize flavonoids as a result of their own endogenous metabolism [18]. The biocatalytic production of flavonoids offers many advantages, such as fast production, low environmental pollution, and large-scale production.…”
Section: Introductionmentioning
confidence: 99%
“…IR spectra characteristically revealed the existence of peaks for conjugated carbonyl groups at 1658 cm −1 . 1 H NMR spectra obviously showed two doublet signals corresponding to the vinyl protons CH = CH–CO with coupling constant 15.6–15.7 Hz indicating trans configuration 46 , 47 . Also, 13 C NMR spectra showed the presence of carbonyl carbon at δ 188.4–188.9 ppm along with trans olefinic carbons at δ 144.2–143.9 and δ 121.2–121.6 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…During our previous study, it was observed that licochalcones B, C, H could be O-glucosylated by using the fungus M. hiemalis [27]. Here, the same process was performed with LCA and XN, which led to the isolation of a new compound licochalcone A 4-O-β-D-glucopyranoside (6) together with a known compound xanthohumol 4 -O-β-D-glucopyranoside [28].…”
Section: Microbial Transformation Of Licochalcone a And Xanthohumol By M Hiemalismentioning
confidence: 97%
“…To the best of our knowledge, no metabolism studies of licochalcones B-D and H were performed so far, except the study previously carried out in this lab [27]. Thus, in order to identify the conjugated metabolites of licochalcones, further studies need to be performed.…”
Section: Introductionmentioning
confidence: 99%